2003
DOI: 10.1186/1471-2156-4-s1-s103
|View full text |Cite
|
Sign up to set email alerts
|

A genome-wide scan to identify loci for smoking rate in the Framingham Heart Study population

Abstract: Background: Although many years of genetic epidemiological studies have demonstrated that genetics plays a significant role in determining smoking behavior, little information is available on genomic loci or genes affecting nicotine dependence. Several susceptibility chromosomal regions for nicotine dependence have been reported, but few have received independent confirmation. To identify susceptibility loci for nicotine dependence, 313 extended pedigrees selected from the Framingham Heart Study population wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
106
0

Year Published

2005
2005
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(111 citation statements)
references
References 10 publications
5
106
0
Order By: Relevance
“…Although the prevalence of smoking has decreased significantly in many countries, particularly among men, the number of highly dependent smokers has not declined correspondingly. 28 In previous linkage analyses, smoking behavior as a phenotype has been defined in several different ways: average 7,15 or maximum 29,30 number of cigarettes smoked per day, ever smoking, 31 habitual smoking 17,18 and total number of cigarette packs per day for 1 year. 14 Similarly, ND can be defined in various ways, the most commonly used definitions being based on the DSM-IV 32 and the FTND.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the prevalence of smoking has decreased significantly in many countries, particularly among men, the number of highly dependent smokers has not declined correspondingly. 28 In previous linkage analyses, smoking behavior as a phenotype has been defined in several different ways: average 7,15 or maximum 29,30 number of cigarettes smoked per day, ever smoking, 31 habitual smoking 17,18 and total number of cigarette packs per day for 1 year. 14 Similarly, ND can be defined in various ways, the most commonly used definitions being based on the DSM-IV 32 and the FTND.…”
Section: Discussionmentioning
confidence: 99%
“…However, ascertainment criteria as well as study samples have been diverse, and not surprisingly, only a few findings seem consistent across studies. Depending on the study population and the phenotype criteria used, some evidence of linkage (logarithm of the odds (LOD)/Z scores X2) for ND has been reported on chromosomes 2, 6, 7, 8, 10, 11 and 18, [10][11][12][13] linkage for smoking rate on chromosomes 3, 4, 5, 10, 11 and 17, 7,[12][13][14][15][16] and linkage for ever smoking, habitual smoking or smoking initiation on chromosomes 6, 9 and 11. 7,[16][17][18] Thus, suggestive findings for smoking-related loci exist for most chromosomes.…”
Section: Introductionmentioning
confidence: 99%
“…Animal studies have suggested a role for the GABA B receptor in nicotine reward, 148 and the gene encoding the GABA B2 subunit is located at chromosome 9q22 in a region which has shown suggestive linkage to ND (Table 1). 46 Significant associations were found for SNPs and haplotypes in GABAB2 with ND in both African Americans and European Americans. 149 The opiate system is important for the rewarding properties of nicotine and may be involved in drug craving.…”
Section: Other Likely Candidates Involved In Neurotransmitter Systemsmentioning
confidence: 97%
“…39 Loci identified with other smoking phenotypes also contain some biologically interesting candidates, such as a region on chromosome 5q located near the dopamine receptor (D 1 ) gene, which has been reported in several studies. 32,40,41 Regions on chromosomes 6, 9 and 11 26,32,33,[40][41][42][43][44][45][46] are also promising as several studies have replicated the linkage and these regions contain some potential biologically relevant candidate genes (Table 1).…”
Section: Genome-wide Linkage Studiesmentioning
confidence: 99%
“…2 A number of linkage and association studies have identified susceptibility genes for ND; 3,4 however, few association studies of candidate genes and/or linkage analyses for susceptibility loci have been replicated in independent samples. 3,5 Previously, we identified several chromosomal regions that are likely to harbor susceptibility loci for ND in the Framingham Heart Study (FSH) and Mid-South Tobacco Family (MSTF) samples, including one region on chromosome 11q13 and one on chromosome 17p13, 3,[6][7][8] where the two genes of interest, b-arrestins 1 and 2 (ARRB1 and ARRB2), are located, 9,10 respectively. b-arrestins are key negative regulators and scaffolds for G-protein-coupled receptor (GPCR) signaling, one of the most fundamental cellular signal transduction processes.…”
mentioning
confidence: 99%